ANALISIS USAHA PENANGKAPAN UDANG REBON (Acetes sp) DENGAN ALAT TANGKAP SONDONG DI PESISIR GAMPONG PASAR ACEH KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT - Amarullah Amarullah (Jurnal Perikanan Terpadu, 2018)
Rebon is one of the results of kind crustaceans but with a very small size compared with other types of crustaceans. Because of its small size it is, these shrimp with shrimp called "rebon". In foreign countries, the shrimp is better known for shrimp because shrimp paste is the main raw material of making paste. In any market, the shrimp is more easily found as ingredients such as shrimp paste, or have been dried and very rarely sold in a fresh state (Astawan, 2009).the average cost of fixed (Fixed Cost) ie depreciation of the fishing gear, vehicle depreciation and maintenance of fishing gear in shrimp fishing effort Rebon by fishermen in coastal Aceh Market for Rp.2.719.044.Gampong variable cost average that is issued by Coastal fishing GampongPasar Aceh covering operational costs of fuel consumption and smoking of Rp.5.211.808.Dari research with shrimp fishermen RebonGampongPasar Aceh coastal region, the average amount of profit in a month against the catch shrimp Rebon with Sondong fishing gear for Rp.2.719.611 fisherman. The results of the calculation of the R / C ratio on shrimp fishing effort tanggkap tool SondongRebon with an average value of 2.97 values greater than one (R / C> 1), which means that fishing effort is worth doing. According to Herman, (1998). Shrimp fishing effort is already profitable and that means that on average each fishing shrimp in gaining the acceptance of 2,97 time  fold up costs.Keywords: Shrimp Rebon, Business Analysis Arrest